Comparative Analysis of Oral Nifedipine Versus Oral Progesterone Alone in the Treatment of Threatened Preterm Labor (Medical Forum Monthly, 2021)
Objective: To compare the effectiveness of oral nifedipine versus oral progesterone alone in the treatment of threatened preterm labor from 24 to 37 weeks of gestation.Study Design: Experimental StudyPlace and Duration of Study: This study was conducted at the Department of obstetrics and gynecology of Al-Tibri Medical College and Hospital and Kulsoom Bai Valika Social Security Hospital, Karachi in the duration of four months from November 2020 to February 2021.Materials and Methods: A total of 188 patients with threatened preterm labor having age 18-40 years with singleton pregnancy, gestational age between 24-37 weeks confirmed by LMP or ultrasound were included and divided into two groups. Groups A (n=94) was treated with the 20mg of oral nifedipine three times for 48 to 72 hours and Group B (n=94) was treated with the 100mg oral progesterone twice daily for 72 hours. Success in stopping uterine contractions was defined as absence of any contraction after 12 hours of treatment. Data was collected into predesigned Performa.Results: The average age of women in group A was 27.59±5.41 and in group B was 28.11±5.37 years. Mean gestational age was 33.05±3.59 weeks. Effectiveness of a drug (Success in stopping uterine contractions is defined as no contractions after 12 hours) was significantly high in group A than group B (76.8% vs. 66%; p=0.0005).Conclusion: Nifedipine seems to be effective and safe tocolytic agent; it can be used successfully to inhibit contractions in threatened preterm labor.